2023
DOI: 10.3390/medicina59091527
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis Comparing the Effectiveness of Transversus Abdominis Plane Block and Caudal Block for Relief of Postoperative Pain in Children Who Underwent Lower Abdominal Surgeries

Dan Xiao,
Yiyuan Sun,
Fang Gong
et al.

Abstract: Background and Objectives: Postoperative pain after lower abdominal surgery is typically severe. Traditionally, in pediatric anesthesia, a caudal block (CB) has been used for pain management in these cases. Nowadays, a transversus abdominis plane block (TAPB) seems to be an effective alternative. However, which technique for perioperative analgesia is better and more effective remains unclear in children who undergo abdominal surgeries. The aim of this study was to compare the efficacy and safety of a TAPB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…[ 11 ] However, other studies reported that some peripheral blocks were superior to caudal blocks in other surgeries. [ 12 , 13 , 14 , 15 ] Regarding pull-through surgery in patients with HD, a previous study reported better postoperative analgesia and more stable intraoperative haemodynamics in the patients who underwent the surgery under combined general–caudal anaesthesia compared with those who underwent the surgery under only general anaesthesia. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] However, other studies reported that some peripheral blocks were superior to caudal blocks in other surgeries. [ 12 , 13 , 14 , 15 ] Regarding pull-through surgery in patients with HD, a previous study reported better postoperative analgesia and more stable intraoperative haemodynamics in the patients who underwent the surgery under combined general–caudal anaesthesia compared with those who underwent the surgery under only general anaesthesia. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%